Emissive nature and molecular behavior of zero-dimensional organic-inorganic metal halides Bmpip₂MX₄ - Sun, Ping-Ping (2022)
Zero-dimensional (0D) organic-inorganic metal halides, with their high stability and broadband emission features, have aroused great interest in optoelectronic applications. Metal halides of the type Bmpip₂MX₄ (M = Pb, Sn, or Ge; X = I or Br) have 0D disphenoidal coordinated structures that offer an excellent opportunity to investigate their emissive nature and molecular behavior. Herein, the photophysical properties and carrier transport behavior of 0D Bmpip₂MX₄ metal halides are studied by using density functional theory. Our results indicate that Bmpip₂MX₄ metal halides present broadband emission widths and significant Stokes shifts. In particular, Bmpip₂MX₄ possesses the largest Stokes shift (1.981 eV) and the shortest exciton self-trapping time, demonstrating the best photoluminescence emission ability. Bmpip₂GeI₄ exhibits the lowest electron-hole creation energy and the best photoresponse capacity. Moreover, Bmpip₂PbI₄ demonstrates superior transport capabilities with high carrier mobilities of 4.56 × 10-3 and 2.51 × 10-7 cm2 V-1 s-1 for hole and electron carriers, respectively, which makes it comparable even with typical hole transport materials (e.g., RR P3HT, ∼10-4 cm2 V-1 s-1). These findings highlight exciting opportunities for the future development and application of such kinds of 0D metal halides in optoelectronics.